THE ROLE OF NATIONALITY IN THE GENESIS OF MODERN TURKEY - (:unkn) unknown (My University, 2019)
The relationship of modernization and nationality will be investigated in this article by reference of Turkish political history in the context of approaches of civil, ethnical and modernist nationalism. Modernization beginning with Ottoman State has been continued during Republic era. Nationality appearing especially after French Revolution in the west symbolizes emergence of national states as well as competition of common people in respect of rights and freedoms. Turkism, as well as Ottomanism and Islamism has been very strong in the late Ottoman State. Nationality was crucial element during National Independent Struggle and foundation of the Republic. Development and role of nationality from Ottoman to Republic has been analyzed in this essay in regard of modernization.

Bu araştırmada Türk siyasi tarihi bağlamında modernleşme ve milliyetçilik olgusu arasındaki ilişki sivil, etnik ve modernist milliyetçilik yaklaşımları bağlamında ele alınmaktadır. Osmanlı ile başlayan modernleşme hikayemiz Cumhuriyet ile devam etmiştir. Milliyetçilik Batı’da bilhassa Fransız İhtilaliyle birlikte ulus devlet anlayışının ortaya çıkmasını ve toplumun büyük kısmını oluşturan avam tabakasının siyasal anlamda hak ve hürriyet mücadelesini sembolize etmektedir. Osmanlı’nın sön döneminde İslamcılık ve Osmanlıcılıkla birlikte Türkçülük çok belirgin bir şekilde varlığını hissettirmiştir. İstiklal Mücadelesinde ve Cumhuriyetin kuruluşunda milliyetçilik çok önemli bir saik olmuştur. Bu makalede Osmanlı döneminden Cumhuriyete milliyetçilik olgusunun gelişimi ve rolü modernleşme bağlamında analiz edilmiştir.
MODERN TÜRKİYE’NİN DOĞUŞUNDA MİLLİYETÇİLİĞİN ROLÜ
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel; Film, Radyo, Televizyon; Tarih; Hukuk; İşletme; Sosyal Çalışma; Sosyoloji